CLIMATE VULNERABILITY OF A NIGERIAN TROPICAL DAM: BIOASSESSMENT OF WATER QUALITY USING MACROINVERTEBRATES IN MICHIKA, ADAMAWA STATE - Abasiryu, Apagu; Hasan, Emmanuel I.; Chaka, Bamaiyi; Mbilari, Mshelia B.; Mohammed, Musa; Filibus, Ngati; Ishaya, Maryam (FUDMA Journal of Sciences, 2026)
Rising environmental pollution from anthropogenic activities poses significant threats to aquatic ecosystems in Nigeria. Heavy metals persist in water and sediments, bioaccumulate, and enter food chains, while benthic macroinvertebrates serve as effective bioindicators for assessing long-term water quality. This study evaluated the climate vulnerability of the Michika mini-dam in Adamawa State by analyzing physicochemical parameters, heavy metal concentrations, and macroinvertebrate community structure. Water and sediment samples were collected biweekly over six months from three stations. Physicochemical parameters were measured using standard methods, and heavy metals (Fe, Zn, Cd, Pb, Cr, Mn, Cu) were analyzed via Atomic Absorption Spectrophotometry. Benthic macroinvertebrates were sampled using a Van Veen grab, preserved in formalin, and identified to species level. Results showed mean dissolved oxygen (DO) levels (5.51-6.31 mg/L) below FMEnv guidelines, while biochemical oxygen demand (BOD₅) levels (2.17-3.27 mg/L) exceeded acceptable limits, indicating organic pollution. Heavy metals in water were detected at levels such as Cd (0.01–0.04 mg/L), Pb (0.02–0.06 mg/L), and Fe (0.68-1.53 mg/L), particularly at Station 3, which was the most contaminated. Sediments contained higher concentrations of metals. A total of 462 macroinvertebrate individuals across 17 taxa were identified, with Diptera (Chironomidae) being the most abundant. Despite the metal contamination, biotic indices rated water quality as good to excellent, highlighting the dam’s moderate pollution stress and the importance of integrated bioassessment for tropical dam management